Accelerating convergence in the antisymmetric product of strongly orthogonal geminals method. Issue 3 (6th March 2012) - Tarumi, Moto; Kobayashi, Masato; Nakai, Hiromi; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Antisymmetric product of strongly orthogonal geminals (APSG) method is a wavefunction theory that can effectively treat the static electron correlation using two‐electron wavefunctions, called geminals. However, the APSG method has the problem of slow convergence in the optimization of the geminal function. In this study, we introduced the direct inversion in the iterative subspace (DIIS) method, for both closed‐ and open‐shell systems, for accelerating its convergence. Two types of error vectors, that is, unitary transformation and orbital gradient, were examined for the DIIS procedure. Numerical assessments revealed that the orbital‐gradient error vector shows better performance than the unitary‐transformation one. © 2012 Wiley Periodicals, Inc.